Entre as proposições teóricas e a prática: o uso da literatura infantil nas escolas municipais de Lagoa Santa - Virginia de Souza Avila Oliveira (2011)
The aim of this study is to discuss the pedagogical practices involving literature activities in school. Its main objective is to analyze the choices of appropriate literary works by teachers for their pupils and the contribution of school librarians; moreover, this work examines the role literature plays in an environment where the children literacy is dealt with in a systematic, thought-provoking way. The research field sites were four local schools in the city of Lagoa Santa, within the greater Belo Horizonte, capital of Minas Gerais state; these schools are included in the Alfaletrar project, which was idealized and implemented by UFMG professor Magda Soares. The methodological procedures aimed for qualitative research; firstly, interviews were made so as to try and understand the general practices involving literature used in that city. Then, four schools were selected for in-depth analysis aiming at understanding how the theoretical practices proposed by the Literacy Group are actually carried out in the school routine. The analysis of data reveals that there are significant differences in the way schools adopt children literature activities, although all of them have an active role in the studies carried out by the Literacy Group. The final results seem to suggest that the school library is an essential tool for the students learning process, and it has a direct impact on the pedagogical practices used in the pupils literary literacy